A comparative study on outcome of conservative and surgical treatment of type III supracondylar fracture of humerus in children - N., Vinay; A., Manjunatha; B. S., Anand Kumar (International Journal of Research in Orthopaedics, 2020)
Background: Supracondylar fracture of humerus is most common of all the fractures around the elbow in children. They occur most commonly in children more so in male child with the peak around 5-8 years. Objective of this study was to compare the outcome of 3 different modalities of treatment for supracondylar fracture of humerus. Methods: Children with type III supracondylar fracture of humerus were categorized into group A, group B, group C based on conservative, closed reduction and percutaneous K wire fixation and open reduction and K wire fixation modalities of treatment given. All the children were followed for 6 months and the outcome of treatment was evaluated using Flynn’s criteria. Results: 40 children were treated with 3 different modalities of treatment. The rate of complications was less in children who were operated on first day of admission (p=0.02). Group B and group C had 80% and 61.11% excellent results and group A had 47.05% poor results. The outcome was better with cross K wire pinning than lateral pinning (p=0.015). Conclusions: Supracondylar fracture of humerus should be operated as early as possible to reduce the rate of complications. The outcome of surgical treatment was better than conservative treatment evaluated in terms of Flynn’s criteria. Cross wire pinning was better than lateral pinning in terms of outcome, but the rate of neuropraxias was more with cross wire pinning.